The work values of Malaysian graduates: Scale development and validation - Mohamad, Bahtiar; Zulkepli Hew, Jafri; Ismail, Ahmed Rageh; Abu Bakar, Hassan (Institute of Advanced Scientific Research, 2019)
Culture plays an integral role in shaping our values and beliefs which are eventually used as our guiding principles for justifying our actions and behaviours. Generally, studies on values have continued to attract enormous attention of both academics and practitioners most especially as the trend of internationalization and globalization continue to increase, work values have become an important medium through which employee behaviour can be understood and managed. Therefore, the current study draws on a literature review to propose a model that can depict work value variables and dimensions of Malaysian graduate students. As such, this study adopts a four-stage process of item development and validation. The result of the Exploratory Factor Analysis (EFA) revealed that Malaysian graduates work values involves are of three dimensions namely; (1) comfort and security; (2) competence and growth; and (3) status and independence. The results of this study will help the management of Malaysian universities in developing their course learning outcome in a way that enhances the Malaysian graduates work values and eventually increase their employability rate.